Transcriptome Analysis of Polyhydroxybutyrate Cycle Mutants Reveals Discrete Loci Connecting Nitrogen Utilization and Carbon Storage in Sinorhizobium meliloti - Maya D’Alessio (American Society for Microbiology, 2017)
ABSTRACT Polyhydroxybutyrate (PHB) and glycogen polymers are produced by bacteria as carbon storage compounds under unbalanced growth conditions. To gain insights into the transcriptional mechanisms controlling carbon storage in Sinorhizobium meliloti, we investigated the global transcriptomic response to the genetic disruption of key genes in PHB synthesis and degradation and in glycogen synthesis. Under both nitrogen-limited and balanced growth conditions, transcriptomic analysis was performed with genetic mutants deficient in PHB synthesis (phbA, phbB, phbAB, and phbC), PHB degradation (bdhA, phaZ, and acsA2), and glycogen synthesis (glgA1). Three distinct genomic regions of the pSymA megaplasmid exhibited altered expression in the wild type and the PHB cycle mutants that was not seen in the glycogen synthesis mutant. An Fnr family transcriptional motif was identified in the upstream regions of a cluster of genes showing similar transcriptional patterns across the mutants. This motif was found at the highest density in the genomic regions with the strongest transcriptional effect, and the presence of this motif upstream of genes in these regions was significantly correlated with decreased transcript abundance. Analysis of the genes in the pSymA regions revealed that they contain a genomic overrepresentation of Fnr family transcription factor-encoding genes. We hypothesize that these loci, containing mostly nitrogen utilization, denitrification, and nitrogen fixation genes, are regulated in response to the intracellular carbon/nitrogen balance. These results indicate a transcriptional regulatory association between intracellular carbon levels (mediated through the functionality of the PHB cycle) and the expression of nitrogen metabolism genes. IMPORTANCE The ability of bacteria to store carbon and energy as intracellular polymers uncouples cell growth and replication from nutrient uptake and provides flexibility in the use of resources as they are available to the cell. The impact of carbon storage on cellular metabolism would be reflected in global transcription patterns. By investigating the transcriptomic effects of genetically disrupting genes involved in the PHB carbon storage cycle, we revealed a relationship between intracellular carbon storage and nitrogen metabolism. This work demonstrates the utility of combining transcriptome sequencing with metabolic pathway mutations for identifying underlying gene regulatory mechanisms. Author Video: An author video summary of this article is available.